Improving flexural characteristics of 3D printed geopolymer composites with in-process steel cable reinforcement - Lim, Jian Hui (2018)
3D concrete printing has recently become the subject of very rapidly growing research activities all over the world. An obstacle to develop 3D concrete has been the lack of tensile strength and therefore, limiting the printed component for structural application. This can be partly solved by designing fiber reinforced concrete or concrete with in-process embedded steel reinforcement. This article presents our first findings of using a steel cable reinforcing nozzle which can directly entrain continuous steel cable inside any extrudable mortar (e.g geopolymer), thus creating a hybrid reinforcement, that will improve flexural strength and ductility of the geopolymer composite. We have tested different cable reinforcements and compared their performance based on 4-point bending test. From experimental results, it was found that steel cables can provide a suitable reinforcement and hence improve the flexural strength of 3D printed concrete by 290%. Further research into optimal reinforcement placement, configuration and reinforcement material is recommended.